Physicochemical Properties of Ionic Liquid Mixtures - Zhang, Suojiang; Zhou, Qing; Lu, Xingmei; Song, Yuting; Wang, Xinxin (Springer Netherlands : Imprint: Springer, 2016)
This handbook is a valuable resource for scientists, engineers, graduate students, managers, decision makers, and those who are interested in ionic liquids. Many industrial applications rely on the use of Ionic Liquid Mixtures, as in solar energy storage, waste recycling or batteries. Physicochemical Properties of Ionic Liquid Mixtures is a useful handbook that contains the following features: - the physicochemical properties and property models of mixtures containing ionic liquids - supplemented by a comprehensive database of properties listing ionic liquid systems collected from more than 800 dependable literature sources - over 60,000 data entries on 39 types of physicochemical properties for 1388 mixtures, including binary, ternary, quaternary and other mixtures. .